Quantifying the Impact of Spectral Coverage on the Retrieval of Molecular Abundances from Exoplanet Transmission Spectra. (6th September 2017) - Chapman, John W.; Zellem, Robert T.; Line, Michael R.; Vasisht, Gautam; Bryden, Geoff; Willacy, Karen; Iyer, Aishwarya R.; Bean, Jacob; Cowan, Nicolas B.; Fortney, Jonathan J.; Griffith, Caitlin A.; Kataria, Tiffany; et al.
Abstract: Using forward models for representative exoplanet atmospheres and a radiometric instrument model, we generated synthetic observational data to explore how well the major C- and O-bearing chemical species (CO, CO2, CH4, and H2 O), important for determining atmospheric opacity and radiation balance, can be constrained by transit measurements as a function of spectral wavelength coverage. This work features simulations for a notional transit spectroscopy mission and compares two cases for instrument spectral coverage (wavelength coverage from 0.5–2.5 μ m and 0.5–5 μ m). The simulation is conducted on a grid with a range of stellar magnitudes and incorporates a full retrieval of atmospheric model parameters. We consider a range of planets from sub-Neptunes to hot Jupiters and include both low and high mean molecular weight atmospheres. We find that including the 2.5–5 μ m wavelength range provides a significant improvement in the degree of constraint on the retrieved molecular abundances: up to ∼3 orders of magnitude for a low mean molecular weight atmosphere ( μ = 2.3) and up to a factor of ∼6 for a high mean molecular weight atmosphere ( μ = 28). These decreased uncertainties imply that broad spectral coverage between the visible and the mid-infrared is an important tool for understanding the chemistry and composition of exoplanet atmospheres. This analysis suggests that the James Webb Space Telescope's (JWST) Near-Infrared Spectrograph (NIRSpec) 0.6–5 μ m prism spectroscopy mode, or similar wavelength coverage with possible future missions, will be an important resource for exoplanet atmospheric characterization.